2004
DOI: 10.1111/j.1365-2249.2004.02651.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the cytokine receptors for human interleukin (IL)-12 and IL-18 on lymphocytes of both CD45RA+ and CD45RO+ phenotype from tonsils, cord and adult peripheral blood

Abstract: SUMMARYThe objective of this study was to demonstrate the variable expression of cytokine receptors on naive versus memory human CD4+ T cell subpopulations in tonsillar tissue, cord blood and adult blood. We prove that the receptors for both interleukin (IL)-12 and IL-18 are expressed exclusively on memory T cells. This observation was seen not only on the CD45RO + memory T cells but also on a significant percentage of the CD45RA-, CD27 -and CCR7 -populations. Furthermore, CD45RA+ or CCR7 + CD4 + T cells that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…In accordance with earlier studies, 19 we were not able to detect IL-12R␤2 expression on resting memory Th cells by flow cytometry (data not shown). To detect low but functional IL-12 receptor expression in IL-18R␣ ϩ and IL-18R␣ Ϫ memory Th cells purified from peripheral blood, we assessed IL-12R-dependent STAT4 phosphorylation (pSTAT4) by immunoblotting.…”
Section: Cytokine-induced Ifn-␥ Secretion Is Confined To Ccr7 ؊ Ccr5 supporting
confidence: 76%
See 1 more Smart Citation
“…In accordance with earlier studies, 19 we were not able to detect IL-12R␤2 expression on resting memory Th cells by flow cytometry (data not shown). To detect low but functional IL-12 receptor expression in IL-18R␣ ϩ and IL-18R␣ Ϫ memory Th cells purified from peripheral blood, we assessed IL-12R-dependent STAT4 phosphorylation (pSTAT4) by immunoblotting.…”
Section: Cytokine-induced Ifn-␥ Secretion Is Confined To Ccr7 ؊ Ccr5 supporting
confidence: 76%
“…26,33 So far, functional IL-12R expression among Th cells was exclusively attributed to recently activated Th1 cells. 19 We demonstrate, however, that functional receptors for IL-12 are also expressed by resting peripheral IL-18R␣ ϩ Th cells reflected by STAT4 phosphorylation on IL-12 stimulation. Whether the observed receptor expression pattern is stable over time in vivo after initial Th1 polarization or results from recurrent antigenic reactivation is currently under investigation.…”
Section: Discussionmentioning
confidence: 98%
“…IL18R1 (52), NOD2 (53), FLT1 (54), CCL3, CCL5 (55), ITGB7 (56)), many have not been linked specifically to either subset in the literature (AIM2, EMP1, ANK3, MPEG1; Table II). To obtain a more complete understanding of which functions might be regulated by CpG methylation as revealed in our data, functional pathway mapping was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐12 receptor beta 1 (Rβ1) is essential for the enhancement of IL‐12‐mediated alloantigen‐specific immune response 22. It has been reported that IL‐12 receptors are expressed more highly in memory rather than in naive T cell subsets after the activation of T cells 23. Here, we investigated how preoperative levels of IL‐12Rβ1 + cells influence the phenotype and function of CD8 + T cell subpopulations after LDLT, associated with changes of IFN‐γ, tumor necrosis factor‐alpha, and perforin expression.…”
mentioning
confidence: 98%